The complete mitochondrial genome of Neolissochilus benasi (Cypriniformes: Cyprinidae) - Gu, Wei (Mitochondrial DNA B Resour, 2020)
In this study, the complete mitochondrial genome of Neolissochilus benasi has been determined by polymerase chain reaction method for the first time. The overall base composition of N. benasi mitogenome is 31.8% for A, 27.4% for C, 15.9% for G and 25.0% for T. The percentage of G + C content is 41.3%. The mitogenome is a circular DNA molecule of 16 583 bp in length with a D-loop region and contains 22 transfer RNA (tRNA) genes, two ribosomal RNA (rRNA) genes and 13 protein-coding genes. The mitochondrial genome sequencing for N. benasi in this study provides important molecular data for further evolutionary analysis for Cyprinoidea.